ANALYSIS OF ECONOMIC STRUCTURE TRANSFORMATION IN EAST KUTAI DISTRICT EAST KALIMANTAN PROVINCE 2012-2022 - Abddurrahmat Hasyim; Didit Welly Udjianto (International Journal of Multidisciplinary Research and Literature, 2023)
High economic growth is a sign of good social welfare. The total added value generated by all business units in an area is known as GRDP. Meanwhile, existing resources can be simplified and focused on the growth of sectors that have multiple impacts on other sectors during the regional economic development process. This study aims to determine the potential of leading sectors, changes and shifts in industries, and the position of economic sectors based on their growth and contribution in East Kutai Regency for the 2012-2022 period. The techniques used are location quotient (LQ) analysis, shift share, and growth ratio model (MRP). This quantitative study used secondary data as time series of the Gross Regional Domestic Product (GRDP) of East Kutai Regency and East Kalimantan Province from 2012-2022. The results of the Location Quotient analysis show that the mining and quarrying sector is the basic sector in East Kutai Regency. Based on the results of the shift-share study of the seventeen economic sectors, progress has been rapid from year to year, so there has been a shift in the financial industry. The results of the analysis of the growth ratio model (MRP) show that the dominant growth sectors are the agriculture, forestry, and fisheries sectors, the electricity and gas procurement sector, the water supply sector, waste processing, waste, the construction sector, the wholesale and retail trade sector, the transportation and warehousing sector. Accommodation provision sector, information and communication sector, financial and insurance services sector, real estate sector, corporate services sector, government administration sector, education services sector, health services sector and social activities, and other service sectors